A comparative study of the gastric ossicles of Trichodactylidae crabs (Brachyura: Decapoda) with comments on the role of diet and phylogeny in shaping morphological traits - de Azevedo Carvalho, Débora (2018)
The gastric armature of decapod foregut is a feeding structure that sparks controversial debates about the role dietary and historical components have in shaping its morphological traits. Having previous information about the natural diet is an interesting way to gather evidence on this issue. For the present study, we analyzed the morphological traits of gastric ossicles involved directly in the maceration of food in nine species of freshwater crabs of the family Trichodactylidae (Brachyura: Decapoda) representing five genera, three tribes and two subfamilies. The analyzed gastric ossicles were quite consistent among closely related species, suggesting that the observed traits had a clear phylogenetic component. However, it was also noted that the morphological traits of the gastric teeth of trichodactylid crabs match well with the natural diet and presented likeness with general features of other species with a similar trophic habit. We discuss the influence of phylogeny and function on the design of morphological traits and propose to quantify the role of phylogeny and function in shaping morphological traits through the analysis of phylogenetic signals.